2012
DOI: 10.2214/ajr.11.6751
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Optimal Management of Hepatic Arterial Infusion Chemotherapy After Pancreatectomy for Pancreatobiliary Cancer

Abstract: Our findings suggest that HAI chemotherapy after pancreatectomy is feasible and tolerable, although caution is required particularly after pancreaticoduodenectomy or after total pancreatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, timely adjuvant chemotherapy is still essential for patients with high-risk factors or who have already experienced early liver metastasis, and the relevant theoretical evidence will be further studied in our center. Although no standard adjuvant chemotherapy for PDAC has been established, several gemcitabine-based adjuvant therapies have been investigated [ 21 ], and previous studies reported that systemic intra-arterial chemotherapy appeared to be effective against liver metastasis [ 22 , 23 ]. Furthermore, hepatectomy for recurrent PDAC was applied in a German national cancer center and was proven to be safe and beneficial [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, timely adjuvant chemotherapy is still essential for patients with high-risk factors or who have already experienced early liver metastasis, and the relevant theoretical evidence will be further studied in our center. Although no standard adjuvant chemotherapy for PDAC has been established, several gemcitabine-based adjuvant therapies have been investigated [ 21 ], and previous studies reported that systemic intra-arterial chemotherapy appeared to be effective against liver metastasis [ 22 , 23 ]. Furthermore, hepatectomy for recurrent PDAC was applied in a German national cancer center and was proven to be safe and beneficial [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant chemotherapy is common, and there are few reports where HAIC was used as a treatment for postoperative liver metastases. Hashimoto et al (11) performed HAIC using 5-FU combined with systemic GEM for liver metastases after pancreatectomy in nine patients. In their report, the overall response and disease control rates were 44.4% and 88.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic artery infusion chemotherapy has been used in the adjuvant setting to prevent hepatic recurrence after resection of pancreatic primaries. [41][42][43] Hashimoto et al described use of hepatic artery infusion chemotherapy in nine patients with liver metastases from pancreatic adenocarcinoma and in 42 patients without liver metastasis for prevention of hepatic metastases. 43 Overall, patients received a median of nine courses with a median duration of 89 days.…”
Section: Hepatic Artery Infusionmentioning
confidence: 99%
“…[41][42][43] Hashimoto et al described use of hepatic artery infusion chemotherapy in nine patients with liver metastases from pancreatic adenocarcinoma and in 42 patients without liver metastasis for prevention of hepatic metastases. 43 Overall, patients received a median of nine courses with a median duration of 89 days. Toxicities were hepatic arterial occlusion (2%), hepatic artery stenosis (19.6%), liver abscess or biloma (5.9%), catheter dislocation (5.9%), and wound infection (3.9%).…”
Section: Hepatic Artery Infusionmentioning
confidence: 99%